La adjetivación del paisaje sonoro del Maestro Roncador en la Arquitectura y el Urbanismo (2023)
Soundscapes present a high variability, both physical and temporal. They include those belonging to natural and meteorological phenomena, but are more important when we refer to biotic elements and natural ecosystems. They spread throughout the planet, and vary with the construction and transformation that human beings carry out of everything around them, and the evolution of the languages ​​that they use for their communications. This variability also encompasses this fourth dimension. In this article, a debate is carried out on how to understand the soundscape by the protagonist of the work "Paisajes Sonoros del Maestro Roncador" edited by the SEA in February 2020, and the initial of the "Maestro Roncador", edited by the SEA in 2014, and the adjectives and sound characters that can be given to the different spaces are put into solfa, especially now after the irruption of the silence imposed by the confinement of the pandemic that we have suffered from the coronavirus.